STUDENTS’ LEVEL OF THINKING SKILLS IN ACADEMIC READING SUBJECT AT THE FOURTH SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM - Camerling, Bella; Tuasela, Patrick (Pattimura University, 2025)
This study is focused on the analysis of students’ level of thinking skills in academic reading subject at the fourth semester of English education study program. This study was designed to describe the level of students thinking skills whether in low-order thinking skill, medium-order thinking skill or high-order thinking skill. The subject of this research was students of Academic Reading Class in English Education Study Program at Pattimura University comprised of 20 students. The data was collected from questionnaire, test, and interview. The research methodology used in this research was descriptive quantitative research design. The study concludes with the result that students’ level of thinking skills are still in the low level and need improvement to achieve high-order level of thinking skill. In addition, to help improve the students’ level of thinking, it should become awareness for the instructor and also the students. Further researchers could investigate more on the need of strategies or procedure to face difficulties and challenges in empowering students’ level of thinking from LOTs to HOTs.